Analisis Dampak Durasi Bermain Game Online Terhadap Penglihatan Mata Anak Remaja di Desa Ujung Karang - Oktarini, Anisa; Husin, Hasan; Samidah, Ida; Yanuarti, Riska (Avicenna: Jurnal Ilmiah, 2025)
Background: Online games are a type of game that involves several internet users in various places connected to each other, in Ujung Karang Village teenagers play online games for more than 5 hours/day so that they experience decreased visual acuity due to excessive gaming habits. This study aims to examine the duration of Teenagers' eye health and playing online games in Ujung Karang Village. Method: A case control technique combined with observational analytics is used in this study. Purposive sampling is used to gather samples based on predetermined criteria, and the case control design is used to evaluate the degree of risk to the eye health of teenagers in Ujung Karang Village. Result: Based on the study's findings, the chi-square test indicates that the p value is 0.043. Therefore, it may be said that there is a connection between the variable of duration of playing online games and the variable of eye vision in adolescents in Unung Karang Village and the OR value obtained is 4.375 that the duration of playing online games has an effect on eye vision in adolescents in Ujung Karang Village.Conclusion: It is recommended to limit the duration of playing online games so that it is not excessive, and to routinely take eye breaks while playing, such as implementing To lower the risk of eye health issues, follow the 20-20-20 rule, which states that every 20 minutes when staring at a screen, take a 20-second break to gaze at anything 20 feet away.. Keywords: Online games, Teenagers, Eye health